The effect of blended learning application with flipped classroom method on student learning outcomes in biology learning at SMA Negeri 9 Sinjai - Izzah, Nur Aqidatul; Syamsudduha, St.; Arif, Wiwin Pramita (Universitas Islam Negeri Alauddin Makassar, 2023)
Educators need the right learning media to overcome the problems of the learning system, especially in Biology subject matter of the human circulatory system. The purpose of this study was to examine the effect of applying blended learning with the flipped classroom method on student learning outcomes in biology learning at SMA Negeri 9 Sinjai. The type of research used is a quasi-experimental with random selection of groups (random sampling). The data collection technique used is a test technique in the form of pretest-posttest. The pretest was conducted to collect data on the students' initial abilities, while the posttest was conducted to test the effect of treatment. In this study, differential statistical tests and 3 statistical tests were carried out, namely normality test, homogeneity test, and hypothesis testing. The results of the study indicate that there is a significant effect on the application of blended learning with methods flipped classroom on student learning outcomes at SMA Negeri 9 Sinjai. The hypothesis in this study can be said to be proven because 0.000 < from 0.05 or by looking at the t count of 7.648 while the t table is 2.018, thus t count > ttable. This means that there is a significant influence between the learning outcomes of students who are taught by applying blended learning with the flipped classroom method and students who are taught without applying blended learning with the flipped classroom method.